If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = -2 + 11 Reorder the terms: 6 + 3x = -2 + 11 Combine like terms: -2 + 11 = 9 6 + 3x = 9 Solving 6 + 3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 9 + -6 3x = 9 + -6 Combine like terms: 9 + -6 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 6*8w=208 | | 6x+12=41 | | -(4/9)x=2/3 | | 16=f-12 | | 40=j-16 | | 3y-4.6=4y | | 4.4m+6.2=-8.8m-1.8 | | 4(5+b)=-12 | | x-12=5.2 | | 3y=12x-27 | | 3x+36-5=1+6v | | 7x^2+15x=18 | | 67=3.9r | | 3(2z-1)=4z-2 | | 29+3y=4.5+.5y | | 0.2x-3=-3.14 | | 4(5+b)=12 | | 16=f+12 | | -2.6(14-x)=15.6 | | 27a^3+18a^2=3a | | 76-2x=13-9x | | 10y-50=-150 | | x-3y=29 | | 50x^2=98 | | 5/9n-2=2/3n | | -14=-7x+2(6x-22) | | 2x=6.8 | | 7(6-3x)+2= | | 72=4.5n | | -4v-2v-16=38 | | lnx+ln(x+5)=ln(8x+10) | | -x-42=-3x+14 |